Does the nutritional value of the paleo diet meet the recommendation for professional athletes? - Pieta, A.; Mazur-Kurach, P.; Szot, M.; Fraczek, B. (27th Annual Congress of the European College of Sport Science (ECSS), Sevilla, 30. Aug - 2. Sep 2022, 2022)
INTRODUCTION: Paleolithic nutrition is based on the principles of evolutionary biology with a focus on the moderate carbohydrate options available to hunter-gatherers. The relatively small amount of carbohydrates in the Paleo diet is increasingly used by athletes with the aim of using fat during exercises and saving carbohydrate reserves. The purpose of the study was to evaluate the nutritional value of the isocaloric Paleo diet according to recommendations dedicated to professional athletes.